Faktor-Faktor yang Mempengaruhi Derajat Kecacatan Kusta - Fauziani, Andra Nabila; Anggraini, Dwi Indria; Hanriko, Rizki; Sibero, Hendra Tarigan (Medula, 2024)
Morbus Hansen, also known as leprosy, is an infectious disease that is chronic or chronic. This disease is caused by the acid-fast bacillus (BTA) Mycobacterium leprae which is obligate intracellular. This disease can attack various body systems, including the peripheral nervous system, skin, mucosa, upper respiratory tract, reticuloendothelial system, eyes, muscles and bones. Based on WHO data for 2021, globally there were 133,781 cases of leprosy, with Indonesia ranking third highest in the world with 10,976 new cases after India and Brazil. Leprosy that is not treated properly can cause disability. There are two types of disability in leprosy, namely primary and secondary disability. Primary disability is caused directly by the Mycobacterium leprae bacteria, while secondary disability is a disorder that arises because the primary disability is not treated properly. The level of disability in leprosy is classified based on symptoms of damage to the eyes, hands and feet with levels 0, 1 and 2. Factors that influence the degree of disability in leprosy are grouped into demographic factors, internal factors and external factors. Demographic factors include age, gender, socio-economic status, occupation, and education level. Internal factors include the type of leprosy, length of suffering, number of nerves affected, and leprosy reaction. External factors include compliance with taking medication, delays in treatment, and self-care.